Harnessing the Digital Revolution for Agricultural Succession: A Multi-Site Mixed-Method Study of the 'Petani Muda Keren' (PMK) Community Network and Youth Engagement in Indonesian Food - Andi Fatihah Syahrir; Neva Dian Permana; Muhammad Faiz; Selma Fajic (HM Publisher, 2025)
Indonesia faces a critical agricultural succession crisis, with an aging farmer population threatening the nation's long-term food security (SDG 2). Digital agrifood systems (DAS) are posited as a solution to attract youth, but adoption is uneven, and the socio-structural mechanisms facilitating this transition are poorly understood. This study investigates the role of the 'Petani Muda Keren' (PMK - Cool Young Farmers) community network, a rapidly growing grassroots movement, in bridging this gap. We employed a multi-site (West Java, Yogyakarta, West Sumatra) sequential explanatory mixed-method design. First, a quantitative survey (N=300) was conducted with PMK members (n=150) and a matched control group of non-member young farmers (n=150). We used descriptive statistics, independent t-tests, and Ordinary Least Squares (OLS) regression to analyze differences in digital adoption, productivity, and income. Second, qualitative data from 30 in-depth interviews and 6 focus group discussions with PMK leaders, members, village officials, and Ministry of Agriculture representatives were analyzed using thematic analysis to explain the quantitative findings. PMK members demonstrated significantly (p<0.001) higher adoption scores for digital technologies (such as e-commerce, farm management apps, and IoT sensors). On average, PMK members reported 34.5% higher monthly incomes and 22.8% greater farm productivity compared to non-members. The OLS regression model, controlling for education, farm size, and access to credit, confirmed that PMK membership (β=0.282, p<0.01) is a significant positive predictor of farmer income, distinct from the independent, positive effect of the digital adoption score (β=0.347, p<0.001). Qualitative analysis revealed three core mechanisms: (1) peer-to-peer mentorship de-risking technology adoption, (2) collective action for market access via network-branded e-commerce, and (3) the socio-psychological construction of a modern, 'cool' professional farmer identity. In conclusion, community-based networks like PMK function as critical social infrastructure. They are not merely passive adopters of technology but active